EFEKTIVITAS PENGATURAN DIVERSI DALAM UNDANG-UNDANG NOMOR 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK TERHADAP PERLINDUNGAN ANAK YANG BERKONFLIK DENGAN HUKUM - Sinurat, Asri Vivi Yanti (Smart Education, 2026)
Abstract: Diversion can be understood as a process of transferring the resolution of juvenile criminal cases from the formal criminal justice system to mechanisms outside the court process. Its purpose is to promote restorative justice. Restorative justice directs the resolution of criminal cases by involving the offender, the victim, the families of both parties, and other relevant stakeholders to collectively seek a fair solution that emphasizes restoring the situation to its original condition rather than pursuing retribution (Barda Nawawi Arief, 2008: 45).Based on Article 5 paragraph (2) points (a) and (b) in conjunction with Article 7 of the Juvenile Criminal Justice System Act (UU SPPA), the processes of investigation, prosecution, and adjudication of cases involving children conducted by the General Courts must be directed toward the pursuit of Diversion. In general, the Diversion process is carried out through a deliberative mechanism that takes into account several aspects, including the interests of the victim, the welfare and responsibility of the child, the avoidance of retaliation, social harmony, as well as propriety, morality, and even public order.However, the Diversion process cannot be applied to child offenders who are charged with crimes punishable by imprisonment of seven (7) years or more, as well as to those who are repeat offenders. Outside of these two conditions, investigators, public prosecutors, and judges are obligated to seek the implementation of Diversion[1]. This study aims to examine the application of Diversion within the juvenile criminal justice system and to assess its effectiveness in realizing restorative justice oriented toward the protection of children’s rights and the recovery of victims. The approach employed is normative juridical, involving the analysis of statutory regulations, legal doctrines, and relevant judicial practices. The findings are expected to provide conceptual and practical recommendations for strengthening the implementation of Diversion so that it becomes more consistent, just, and oriented toward the best interests of the child. Keywords: Effectiveness, Diversion, Juvenile Justice System, Child Protection. Abstrak: Diversi dapat diartikan sebagai proses pengalihan penyelesaian tindak pidana anak dari proses peradilan pidana ke proses di luar peradilan pidana. Tujuannya adalah untuk menghadirkan keadilan restoratif (restorative justice). Keadilan restoratif mengarahkan penyelesaian perkara tindak pidana dengan melibatkan pelaku, korban, keluarga pelaku/korban, dan pihak lain yang terkait untuk bersama-sama mencari penyelesaian yang adil dengan menekankan pemulihan kembali pada keadaan semula, dan bukan pembalasan (Barda Nawawi Arief, 2008: 45). Berdasarkan Pasal 5 ayat (2) poin a dan b ko. Pasal 7 UU SPPA, menjelaskan bahwa proses penyidikan, penuntutan, dan persidangan anak yang dilakukan oleh Pengadilan Umum harus mengarah pada upaya Diversi. Secara umum, proses Diversi dilakukan melalui mekanisme musyawarah dengan memperhatikan sejumlah aspek, antara lain kepentingan korban, kesejahteraan dan tanggung jawab anak, penghindaran pembalasan, keharmonisan masyarakat, serta kepatutan, kesusilaan, bahkan ketertiban umum. Namun, proses Diversi sendiri tidak dapat dilakukan kepada terpidana anak yang didakwa penjara 7 (tujuh) tahun atau lebih serta terpidana yang melakukan pengulangan tindak pidana. Di luar kedua ketentuan tersebut, penyidik, penuntut umum, dan hakim wajib mengupayakan proses Diversi[1]. Penelitian ini bertujuan untuk mengkaji penerapan Diversi dalam sistem peradilan pidana anak serta menilai efektivitasnya dalam mewujudkan keadilan restoratif yang berorientasi pada perlindungan hak anak dan pemulihan bagi korban. Pendekatan yang digunakan adalah yuridis normatif dengan menelaah peraturan perundang-undangan, doktrin hukum, dan praktik peradilan yang relevan. Hasil kajian diharapkan dapat memberikan rekomendasi konseptual dan praktis bagi penguatan pelaksanaan Diversi agar lebih konsisten, berkeadilan, dan berorientasi pada kepentingan terbaik bagi anak. Kata Kunci: Efektivitas, Diversi, Sistem Peradilan Pidana Anak, Perlindungan Anak.